Impact of associated factors in adolescent’s psychosocial problems in Banepa: a cross-sectional study - Shrestha, Nishal; Thapa, Janak K.; Chaudhary, Pramodh; Sangroula, Raj K. (International Journal Of Community Medicine And Public Health, 2022)
Background: Adolescence is the lifespan between childhood and adulthood from ages 10 to 19 years. Psychological problem is a state of emotional and behavioral disorders, including depression, anxiety, aggression, educational difficulties, etc. The study aimed to assess the impact of associated factors on adolescents’ psychosocial problems. Methods: Analytical cross-sectional and quantitative method was used. The study population was adolescents in grades 8 and 9. Purposive sampling was used to select the schools and the census technique was used to collect the data from respondents. A structured questionnaire was designed and administered to study participants. Data collected from respondents were analysed and expressed using Epidata 3.1 and SPSS 26. Results: The study shows that the prevalence of psychosocial problems among adolescents was 32.4%. The adolescent age group was greatly dominated by the age group 14-15 years (72.1%) and most of the respondents were female (52%). There was a significant association between the bad relationships with siblings (OR=5.840, 95% CI=1.820-18.735, p value=0.003), neighbors (OR=4.46, 95% CI=1.36-14.60, p value=0.013), classmates (OR=3.630, 95% CI=1.060-12.424, p value=0.040) and fine relationship with teachers (OR=5.091, 95% CI=2.223-11.658, p value<0.001) and those not satisfied with pocket money (OR= 2.833, 95% CI=1.227-6.544, p value=0.015) with the psychosocial problem. Conclusions: The update and revision of mental health policy and increment in the allocation of the health budget are crucial for improving mental health. The school can help by introducing child to parent approach to decrease the prevalence of psychosocial problems through a different awareness program and proper knowledge.